Evaluation of Health Literacy and COVID-19 Knowledge Levels of Candidate Soldiers: A Cross-sectional Study from Ankara, Turkey (Bangladesh Journal of Medical Science, 2024)
people’s COVID-19 knowledge and HL levels are thought to be effective in managing the pandemic. This study aimed to evaluate candidate soldiers’ HL and COVID-19 knowledge levels in the Altındağ district of Ankara, Turkey.Material and Methods  A questionnaire form containing socio-demographic characteristics, 16-item European HL Survey Questionnaire, and propositions about COVID-19 was applied to candidate soldiers Who were referred for COVID-19 PCR sampling to the Altindg District Health Directorate before enlistment between December 2021_April 2022.Results and Discussion  The study was completed with 668 candidate soldiers, most of whom were young adults. HL level of 20.5% was inadequate. The frequency of those who had not been vaccinated against COVID-19 was 16.8%. The COVID-19 knowledge level of those vaccinated was higher (p=0.002). The propositions about COVID-19 symptoms and correct mask use were answered correctly at the highest rate in COVID-19 knowledge level questions. The COVID-19 knowledge level score was significantly higher in those with adequate HL levels, aged 25 and over, non-smokers, and who had university or higher education levels. There was a positive correlation between the COVID-19 knowledge level and HL levels (r=0.108; p